Del mito creacionista al mito futurista - Uhía, Fernando (CALLE14: revista de investigación en el campo del arte, 2011)
The first picture of Earth taken from space in 1946 is one of the signs of the mythological reprograming that is affecting the current perception surrounding the science and the arts. This reprograming opposes a God as artificer to the artist as a creating god: a technological superhuman to an artist that administers Earth. In this reprograming the role of art academies, of scientific revolutions, of vanguard and Pop art are also examined.